FTO suppresses cardiac fibrosis after myocardial infarction via m6A-mediated epigenetic modification of EPRS - Jian Wang; Yanyan Li; Lijie Deng; Yafang Zha; Song Zhang (BMC, 2024)
Abstract Background Cardiac fibrosis is common in myocardial infarction (MI), leading to progressive cardiac dysfunction. Studies suggested that the abnormal N 6-methyladenosine (m6A) modification induced by fat mass and obesity protein (FTO) is vital in MI. However, the effects of FTO on post-infarction cardiac fibrosis have not been detected. Methods Western blot and quantitative real-time PCR were performed to detect the expression of FTO in the fibrotic tissue of rats. The functions of FTO on collagen biosynthesis were analyzed in vitro and in vivo. The underlying targets of FTO were selected through RNA-seq with m6A-seq. The following dual luciferase reporter assay and RNA stability assay were conducted to investigate the mechanisms of FTO-mediated m6A regulation. Results The expression of FTO was decreased in the fibrotic tissue of post-infarction rats. The HIF-1 signal pathway was enriched after MI. HIF-1α could bind to the promoter of FTO and inhibit its expression. Functionally, FTO inhibited collagen synthesis after MI in vitro and in vivo. Mechanistically, EPRS was selected as the underlying target of FTO-induced m6A regulation. IGF2BP3 recognized and bound to the m6A sites of EPRS mRNA, which improved its stability. EPRS was required for cardiac fibrosis induced by FTO silencing. Conclusions FTO, identified as a cardioprotective factor, suppressed collagen synthesis in post-infarction cardiac fibrosis via m6A modification, which provided a new therapeutic strategy for cardiac fibrosis.